Green on Paper, Heavy on Earth: Green on paper, heavy on Earth: Reassessing conservation through the lens of performance and footprint - Hlabisa, Sibongiseni (Ecological Questions, 2025)
This study investigates the relationship between environmental performance and ecological sustainability by analyzing data from 168 countries using two widely recognized indicators: the Environmental Performance Index (EPI) and the Ecological Footprint (EF) per capita. Contrary to common assumptions that strong environmental governance correlates with lower ecological impact, the findings reveal a moderate positive relationship between EPI and EF (Pearson's r = 0.57; Spearman's ρ = 0.65, p < 0.001). This finding suggests that countries with higher EPI scores often exhibit larger ecological footprints, primarily driven by affluence and consumption intensity. Linear regression results further substantiate this link, with EPI emerging as a significant predictor of EF (β = 0.107, p < 0.001), explaining 32.4% of the variance. Cluster and principal component analyses reveal four country typologies, distinguishing between high-performing but high-impact nations and those achieving more sustainable balances. Case studies, including Germany, Saint Lucia, Saudi Arabia, and Guatemala, illustrate the spectrum of governance-impact dynamics. These results challenge the adequacy of governance-centric indicators and highlight the need for integrated sustainability frameworks that combine policy metrics with consumption-based impact measures. By questioning the assumption that environmental performance is synonymous with ecological sustainability, this research calls for a fundamental rethinking of how sustainability is measured, communicated, and pursued in the era of planetary boundaries.